Mereduksi Disfungsional Prokrastinasi Akademik Melalui Layanan Konseling Kelompok Dengan Teknik Behavior Contract - Nur Mahardika (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2020)
The purpose of this study are: 1. Describe the activities of researchers in carrying out group counseling services with behavior contract techniques in reducing the dysfunctional academic procrastination of students of class XI MIPA 2 Senior High School 1 Jakenan, 2. Reducing the dysfunctional behavior of academic procrastination after getting counseling group behavior counseling services for students class XI MIPA 2 SMAN 1 Jakenan. This research was designed using the guidance and counseling action research (PTBK) with the subject of 8 students of class XI MIPA 2 of SMAN 1 Jakenan who have dysfunctional problems of academic procrastination. This type of research is Guidance and Counseling Action Research. Subjects studied were students of class XI MIPA 2 of SMAN 1 Jakenan, as many as 8 students who had dysfunctional academic procrastination behavior Dysfunctional academic procrastination in students can be reduced after group counseling services are provided with a behavior contract technique. This is evident from the pre cycle results obtained an average of 21 with a very high category. While the first cycle obtained an average score of 35 with enough categories. In the second cycle the second cycle obtained a score of 49 with a very low category.